Nondestructive active testing techniques for structural components. (U.S. Dept. of Defense, 1989)
This handbook should serve as a guide to designers concerned with the technology associated with the nondestructive testing of advanced composites. It deals with the basic concepts of nondestructive testing and the specific tests that can be used at various stages during production and in-service inspections. The data can be used by designers to aid in selecting the nondestructive test equipment best suited for a particular application.
Title from title page of source document.
Also available in online version from Department of Defense Single Stock Point for Military Specifications, Standards and Related Publications (DODSSP).
Keywords: Composite materials -- Testing -- Handbooks, manuals, etc.; elektronické knihy; electronic books